STATE REGULATION OF INSURANCE ACTIVITY IN THE CONTEXT OF INNOVATIVE ECONOMIC DEVELOPMENT - Sherov Sanjar Radjabovich (American Journals, 2026)
The article considers the conceptual foundations of the regulators of the institution in the conditions of innovative development of the economy. It notes that the institution as a process of defining and securing norms, rules, statuses, roles is regulated and modeled. On the basis of system analysis, a classification is given which, in the author's opinion, is applicable to research and analysis of the internal structure of the system mechanism with the aim to identify effective forms and instruments of state regulation of insurance activities.
Keywords: Institution, institution theory, insurance institution, institutional regulation tools, direct regulation, indirect regulation, state regulation, methods of state regulation, forms of state regulation, system of state regulation, prudential regulation. institutional regulation tools.